VIRAL MARKETING DITINJAU DALAM PERSPEKTIF HUKUM ISLAM - Solikhah, Solikhah (PARENTAL, 2013)
Business growth is inseparable from the development of technologies that produce innovation ideas in marketing activities. Viral marketing is very rapid in Indonesia by word of mouth as a means of everyday communication make the product widely circulated in the community. However, studies that discussed the viral is still relatively small so the authors are interested in reviewing the review of viral marketing in the perspective of Islamic law. Issues to be discussed in this paper is how a review of viral marketing in the perspective of Islamic law and the application of viral marketing in Indonesia. Based on the analysis results,it is found that Islam supports to make improvements and changes to the trading system of origin is not contrary to Islamic principles. Viral marketing is not contrary to the principles of business development which comprises dharar (danger), jahalah (vagueness) and zhulm (detrimental or unfair to either party) and free from the elements of the Maghrib, the abbreviation of the five elements, namely maysir (gambling), Zhulm (mayhem), Gharar (fraud), unclean, riba (interest), Iktinaz (hoarding), and Bathil (cheating). Viral marketing works like virus replicates that each splitting and so forth that are manyfold. For example Brand as Close Up are releasing viral via twitter with issues close up freshformance the festival become a trend among young quiz realize creative ideas with Joko Anwar movie, Kleting and Shade Umbrella by 5977 as the number of tweets, following 669 and 5630 followers is a portrait that viral marketing has grown in Indonesian society.